Product Evaluation of the Implementation of the Free Nutritious Meal Program for Elementary School Students in Demak Regency: A Qualitative Approach - Musdalifah Nor Amini; Ayun Sriatmi; Apoina Kartini (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
The Free Nutritious Meal Program is a national initiative aimed at improving the nutritional intake of school-aged children to support optimal growth and academic achievement. This study aims to evaluate the product component of the Free Nutritious Meal Program implementation in Demak Regency using the CIPP evaluation model. A descriptive qualitative design was employed. Data were collected through in-depth interviews and direct observations conducted in two beneficiary elementary schools and the Nutrition Fulfillment Service Unit (SPPG) responsible for food distribution. Seven informants were involved, consisting of one SPPI representative, four elementary school students as program beneficiaries, and two teachers as triangulation informants, selected using purposive sampling based on direct involvement in program implementation. The product evaluation indicators included menu diversity, food acceptance, and food freshness (edibility). Observations focused on students’ food consumption behavior, particularly whether meals were finished or left uneaten. The findings revealed limited menu diversity, especially in vegetable variation and cooking methods, with menu repetition occurring approximately once a week. In terms of food acceptance, students tended to prefer savory and familiar local dishes, while certain menus were less favored. Regarding food freshness, meals were generally safe to consume, but their visual appearance was perceived as less fresh and less appealing at the time of serving. These findings indicate the need to improve menu variation, sensory quality, and food presentation. Strengthening menu planning and quality control in accordance with national nutrition guidelines is recommended to enhance the effectiveness and sustainability of the program Keywords: Free nutritious meal program, product evaluation, CIPP model, elementary school, Demak Regency